Pediculate hepatocarcinoma. - Davidenko, Nicolás; Estapé, Gonzalo; Nuchovich, Gustavo; Lombardi, Gerardo Miguel (Cirugía del Uruguay, 1988)
P An excepcase o1 pedlculahepa occurring in a previous pathological liver (massive steatosis) is presentad.